2018
DOI: 10.1111/nmo.13288
|View full text |Cite
|
Sign up to set email alerts
|

The cholinergic anti‐inflammatory pathway revisited

Abstract: Inflammatory bowel disease negatively affects the quality of life of millions of patients around the world. Although the precise etiology of the disease remains elusive, aberrant immune system activation is an underlying cause. As such, therapies that selectively inhibit immune cell activation without broad immunosuppression are desired. Inhibition of immune cell activation preventing pro-inflammatory cytokine production through neural stimulation has emerged as one such treatment. These therapeutics are based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 67 publications
1
27
0
Order By: Relevance
“…Concomitantly, we found that levels of the anti-inflammatory cytokine IL-10 were diminished by splanchnic nerve section (25). Those findings indicate that the splanchnic nerves normally mediate a coordinated physiological antiinflammatory action (24,25,30). The suppressive action against proinflammatory cytokines persists for at least 6 h (25).…”
Section: Introductionmentioning
confidence: 52%
“…Concomitantly, we found that levels of the anti-inflammatory cytokine IL-10 were diminished by splanchnic nerve section (25). Those findings indicate that the splanchnic nerves normally mediate a coordinated physiological antiinflammatory action (24,25,30). The suppressive action against proinflammatory cytokines persists for at least 6 h (25).…”
Section: Introductionmentioning
confidence: 52%
“…With the development of inflammation, an afferent impulse is transmitted along the vagal nerve from the periphery to the brain stem. In the opposite direction, the vagal efferent pathway transmits signals to the spleen, liver, intestines, and other organs [8][9][10][11][12][13][14][15][16]. Stimulation of the efferent vagal nerve, as well as the use of cholinesterase blockers, results in accumulation of acetylcholine in these organs.…”
Section: Pathophysiological Role Of the Ans In The Development Of Sepmentioning
confidence: 99%
“…Therefore, the interaction between cardiac autonomic regulation and swallowing is founded on the parasympathetic nervous system activity 22 . The parasympathetic fibers that exit the vagus nerve are accountable for cardiovascular autonomic regulation 23,24 . The myelinated portion of the vagus nerve provides efferent control of the heart through regulation of the sinus node 25 and this has an impact on HRV during respiratory sinus arrhythmia; when HR increases during inspiration owing to vagal withdrawal and decreases during expiration because of vagal recovery 26 .…”
Section: Discussionmentioning
confidence: 99%